Length-Weight Relationship and Condition Factor Channa Marulioides (Bleeker, 1851) In Kapuas River – West Kalimantan as a Conservation Aquatic Resources Effort: Length-Weight Relationship and Condition Factor of Channa marulioides - Hutagalung, Rizal Akbar; Anggoro, Sutrsino; Suryanti, Suryanti; Muskananfola, Max Rudolf (Journal of Aquaculture and Fish Health, 2024)
Channa marulioides is one of the species that is facing a population decrease due to high fishing activity. This study aims to determine the value of the length-weight relationship and condition factors of C. marulioides in the Kapuas River as a relevant conservation effort. Several sampling areas in this study were used to represent the Kapuas River, including Kapuas Hulu River in Kapuas Hulu Regency, Putussibau District; The central part of the waters area of "‹"‹Sintang Regency in Sintang Regency; and in the downstream waters of Pontianak City. The study carried out the sampling by analyzing the criteria for specimens with a dimension weight > 500 grams and length > 30 cm, with the same amount for each sex. The results showed that the growth type in the upper and middle waters was positive allometric with a value of b 3.1; however, it is negative allometric in the middle and upstream waters with b values "‹"‹of 2.5 and 1.7. After research, the condition factor of the upstream and middle waters was observed to be in good condition with a value of 1. However, in the downstream waters the condition of the fish was rather bad with a value below 1, namely 0.99. The study concludes there is a decrease in the quality of the aquatic environment and the food availability from the middle waters to the downstream. This is what underlines conservation efforts in the form of domestication activities within the scope of structured fish farming.